Arab Republic of Egypt 2010 Article IV Consultation: Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for the Arab Republic of Egypt (IMF Staff Country Reports, 2010)
This 2010 Article IV Consultation highlights that Egypt has weathered the global financial crisis relatively well and financial market pressures have eased after the initial outflow. Equity prices plateaued in recent months, after having recovered over half of the losses since the April 2008 peak. Egypt's sovereign spreads tightened during 2009 and, in early 2010, remain well below their pre-Lehman levels. Reducing the fiscal deficit and public debt are key medium term objectives. Egypt's public debt remains high in comparison with many other emerging market countries